Experimental Evaluation for the Microvibration Performance of a Segmented PC Method Based High Technology Industrial Facility Using 1/2 Scale Test Models - Sijun Kim; Se Woon Choi (Shock and Vibration)
The precast concrete (PC) method used in the construction process of high technology industrial facilities is limited when applied to those with greater span lengths, due to the transport length restriction (maximum length of 15~16 m in Korea) set by traffic laws. In order to resolve this, this study introduces a structural system with a segmented PC system, and a 1/2 scale model with a width of 9000 mm (hereafter Segmented Model) is manufactured to evaluate vibration performance. Since a real vibrational environment cannot be reproduced for vibration testing using a scale model, a comparative analysis of their relative performances is conducted in this study. For this purpose, a 1/2 scale model with a width of 7200 mm (hereafter Nonsegmented Model) of a high technology industrial facility is additionally prepared using the conventional PC method. By applying the same experiment method for both scale models and comparing the results, the relative vibration performance of the Segmented Model is observed. Through impact testing, the natural frequencies of the two scale models are compared. Also, in order to analyze the estimated response induced by the equipment, the vibration responses due to the exciter are compared. The experimental results show that the Segmented Model exhibits similar or superior performances when compared to the Nonsegmented Model.